The Relationship of Immunohistochemical Expression of BRAFV600E with Clinical Features and Histopathological Subtypes in Papillary Thyroid Carcinoma (PTC) - Masriana, Masriana; Betty, Betty; Delyuzar, Delyuzar; Alferraly, Ibnu; Dahlan, Nadjib (Indonesian Journal of Cancer, 2026)
Background: Papillary thyroid carcinoma (PTC) is an indolent thyroid malignancy with clinicopathological features that play a role in prognosis. BRAFV600E mutations in PTC are associated with poor prognosis, and BRAFV600E immunohistochemical staining exhibits high specificity and sensitivity. This study aims to determine the association between BRAFV600E immunohistochemical expression and clinical features and histopathological subtypes in PTC.Method: This analytical observational study utilizes a cross-sectional approach, conducted from March to December 2024 at the Anatomical Pathology Laboratory, Faculty of Medicine, Universitas Sumatera Utara, and affiliated hospitals. A total of 35 PTC samples were selected and continued with BRAFV600E immunohistochemical staining. Clinicopathological data, including age, gender, tumor size, lymph nodes, metastasis, lymphovascular invasion, disease stage, and PTC subtype, were collected. Statistical analysis was performed using Somers'd (ordinal-ordinal) and Eta (nominal-ordinal) correlation test in SPSS.Results: PTC was most prevalent among females and the age group under 45 years. Predominant clinical features included tumor sizes exceeding 4 cm (T3), an absence of lymph node involvement (N0), and no detectable metastasis (M0). The classic subtype emerged as the most frequent histopathological variant, typically presenting without lymphovascular invasion (LVI) and diagnosed at Stage I. While most parameters showed no significant statistical association with BRAFV600E expression (p 0.05), a significant relationship was identified specifically regarding the cancer stage (p 0.05).Conclusion: There are no significant associations observed between BRAFV600E immunohistochemical expression and the majority of clinicopathological factors. However, a significant relationship with disease stage was identified. These findings suggest that BRAFV600E expression may have potential value as an indicator of disease stage in PTC.